Discrimination of oral squamous cell carcinoma from oral lichen planus by salivary metabolomics - Ishikawa, Shigeo; Sugimoto, Masahiro; Edamatsu, Kaoru; Sugano, Ayako; Kitabatake, Kenichiro; Iino, Mitsuyoshi (Oral diseases, 2020)
Objective This study was conducted to distinguish salivary metabolites in oral squamous cell carcinoma (OSCC) from those in oral lichen planus (OLP) to identify practical biomarkers for the discrimination of OSCC from OLP. Subjects and Methods Whole unstimulated saliva samples were collected from patients with OSCC (n = 34) and OLP (n = 26). Hydrophilic metabolites in the saliva samples were comprehensively analysed by capillary electrophoresis mass spectrometry. To evaluate the discrimination ability of a combination of multiple markers, a multiple logistic regression (MLR) model was developed to differentiate OSCC from OLP. Results Fourteen metabolites were found to be significantly different between the OSCC and OLP groups. Among them, indole‐3‐acetate and ethanolamine phosphate were used to develop the MLR model. The combination of these two metabolites showed a high area under the receiver operating characteristic curve (0.856, 95% confidential interval: 0.762–0.950; p < .001) for discriminating OSCC from OLP. Conclusions We identified salivary metabolites for discerning between OSCC and OLP, which is clinically important for detecting the malignant transformation of OLP by both dentists and oral surgery specialists. Our candidate salivary metabolites show potential for non‐invasive screening of OSCC versus OLP.